Exploring the Use of Journal Writing in Mathematics Classroom - Suhaimi, Zuhairina; Shahrill, Masitah; Abbas, Nor 'Arifahwati Haji; Tengah, Khairul Amilin; Roslan, Roslinawati; Yusof, Norashikin (International Journal on Emerging Mathematics Education, 2017)
This paper focuses on secondary mathematics lessons that integrated journal writing with the use of the writing-to-learn pedagogical strategy. Investigations were conducted on the influence of journal writing on Year 10 secondary students' mathematical performance. It is an action research study that comprised of two cycles and involved 35 students from two classes in a secondary school in Brunei Darussalam. The analyses of the data were extracted from the students' pre- and post-test scores and their journal entries. The findings revealed that even though the students' journal entry score was high, this does not necessarily imply improvements in their mathematical performance. Furthermore, other factors such as classwork and homework given during and after the lessons may have also contributed to the students' mathematical achievements.